Development of Mtcu 2+/Ldpe Nanocomposites with Antimicrobial Activity for Potential Use in Food Packaging - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M (2012)
The antimicrobial efficiency of novel MtCu 2+/LDPE nanocomposites against Escherichia coli 0157:H7 n/t was tested in the present work. Montmorillonite modified with copper (MtCu 2+) was obtained using cation exchange in solution and nanocomposite films were prepared by melt mixing in an extruder at 200°C with different compositions. Characterization of MtCu 2+ and MtCu 2+/LDPE nanocomposites was carried out using XRD, AA, TGA, DSC, and microbiological analysis. The clay polymer nanocomposites (CPN) were more stable at higher temperatures, resulting from the incorporation of MtCu 2+ in the polymer. The results indicate that the antibacterial effect of the CPN increases with the proportion of MtCu 2+ added, obtaining a 94% reduction when 4% of MtCu 2+ was added to the polymer. © 2012 Elsevier B.V.